Contribution of portuguese pavement surfaces to traffic noise - Freitas, Elisabete F. (2008)
This paper aims at assessing the relative effect of Portuguese pavement surfaces on traffic noise. It presents the main results obtained with two distinct experiments, originally intended for other purposes, which address a significant number of thin layers and porous layers. These experiments included nine road surfaces: three of them were gap graded, three contained rubberized asphalt, one had porous asphalt and two had dense asphalt. On these road sections the tyre-road noise generated by two-axle heavy trucks and three-axle heavy trucks and several light vehicles at three levels of speed were measured by means of pass-by tests. Surface texture tests were also performed. The results focused on noise level variation versus speed and estimated noise level for each speed level versus type of surface. The best performances were achieved by gap graded mixtures with and without rubberized binder and small grain sizes. The fair behaviour shown by the porous asphalt indicates that the surface texture determined by the grain size seems to influence the noise level more than porosity.